Varicella zoster virus related deaths and hospitalizations before the introduction of universal vaccination with the tetraviral vaccine - Alessandra de Martino Mota; Filipe Anibal Carvalho-Costa (Elsevier, 2016)
Objective: To characterize varicella zoster virus-related deaths and hospitalizations in Brazil before universal vaccination with the tetravalent (measles, mumps, rubella, and varicella) vaccine, attempting to collect baseline data on varicella morbidity and mortality in order to evaluate the impact of the varicella vaccination program. Methods: Varicella-associated mortality data were evaluated between 1996 and 2011 and varicella zoster virus-associated hospitalizations between 1998 and 2013. Data were gathered from the Informatics Department of the Unified Health System, considering the International Classification of Diseases, 10th Revision, code B01. All age groups were assessed. Varicella-specific mortality rates were calculated and seasonality of varicella-zoster virus-associated hospitalizations was described. Results: There were 2334 varicella deaths between 1996 and 2011, 19.3% in infants aged less than 1 year and 36% in children from 1 to 4 years. In infants under 1 year, varicella mortality rates reached 3.2/100,000/year. In children aged 1-4 years, varicella mortality rates reach 1.64/100,000/year. Average annual mortality rates for varicella in Brazil are 0.88/100,000 in infants under 1 year and 0.40/100,000 in children aged 1-4 years. The total number of hospitalizations associated with varicella zoster virus was 62,246 from 2008 to 2013. Varicella-associated hospitalizations have a seasonal distribution in children, peaking in November. In the elderly, monthly averages of herpes zoster-associated hospitalizations present no significant seasonal variation. Conclusions: Varicella is associated, in the pre-vaccine period, to significant morbidity and mortality in Brazil. The universal vaccination program is expected to decrease the disease burden from varicella. Resumo: Objetivo: Caracterizar os óbitos e internações relacionados ao vírus varicela-zoster no Brasil antes da vacinação universal com a vacina tetravalente (sarampo, caxumba, rubéola e varicela), tentando coletar dados de referência sobre a morbidez e mortalidade por varicela, para avaliar o impacto do programa de vacinação contra a varicela. Métodos: Os dados de mortalidade associada à varicela foram avaliados entre 1996 e 2011 e as internações associadas ao vírus varicela-zoster, entre 1998 e 2013. Os dados foram coletados do Departamento de Informática do Sistema Unificado de Saúde, considerando a Classificação Internacional de Doenças, 10ª Revisão, código B01. Todas as faixas etárias foram avaliadas. Foram calculadas as taxas de mortalidade específicas por varicela e foi descrita a sazonalidade das internações associadas ao vírus varicela-zoster. Resultados: Houve 2.334 óbitos por varicela entre 1996 e 2011, 19,3% em neonatos com menos de 1 ano e 36% em crianças de 1 a 4 anos. Em neonatos com menos de 1 ano, as taxas de mortalidade por varicela atingiram 3,2/100.000/ano. Em crianças de 1-4 anos de idade, as taxas de mortalidade por varicela atingem 1,64/100.000/ano. As taxas de mortalidade anuais médias por varicela no Brasil são de 0,88/100.000 em neonatos com menos de 1 ano de idade e 0,40/100.000 em crianças de 1 a 4 anos de idade. O número total de internações associadas ao vírus varicela-zoster foi de 62.246 de 2008 a 2013. As internações relacionadas à varicela apresentaram distribuição sazonal em crianças, com pico em novembro. Em idosos, as médias mensais de internações associadas ao herpes zoster não apresentam variação sazonal significativa. Conclusões: A varicela está associada a morbidez e mortalidade significativas no período pré-vacinação no Brasil. O programa de vacinação universal deve diminuir a carga de doença da varicela. Keywords: Varicella-zoster virus, Varicella, Tetraviral vaccine, Deaths, Hospitalizations, Palavras-chave: Vírus varicela-zoster, Varicela, Vacina tetravalente, Óbitos, Internações